The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1097/01.mat.0000249017.91053.af
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Low Molecular Weight Heparin for Management of Anticoagulation in Infants on Excor Ventricular Assist Device

Abstract: Anticoagulation in infants and children on a ventricular assist device presents particular challenges. Unfractionated heparin has poor bioavailability; it can be difficult to achieve a stable anticoagulant effect; and, in the long-term, there is a risk of osteopenia. Long-term warfarin can be difficult to manage in infants on formula milk with vitamin K supplementation. We review our recent experience with subcutaneous low molecular weight heparin. Two patients received a left ventricular assist device (Excor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…We have continuously improved our anticoagulation management, and since 2007 children remaining in hospital with VAD support have received low-molecular weight heparin for long-term anticoagulation under monitoring of anti-Xa activity, as described by Ghez and colleagues. 11 The target anti-Xa activity is set at between 1.0 and 1.2 IU/mL. After treatment with acetylsalicylic acid and dipyridamole has been initiated (after the start of oral feeding and the removal of chest tubes and in a dose adjusted to patient weight), platelet aggregation tests are performed at least weekly, with target activation of 30%.…”
Section: Anticoagulation During Device Supportmentioning
confidence: 99%
“…We have continuously improved our anticoagulation management, and since 2007 children remaining in hospital with VAD support have received low-molecular weight heparin for long-term anticoagulation under monitoring of anti-Xa activity, as described by Ghez and colleagues. 11 The target anti-Xa activity is set at between 1.0 and 1.2 IU/mL. After treatment with acetylsalicylic acid and dipyridamole has been initiated (after the start of oral feeding and the removal of chest tubes and in a dose adjusted to patient weight), platelet aggregation tests are performed at least weekly, with target activation of 30%.…”
Section: Anticoagulation During Device Supportmentioning
confidence: 99%
“…[15,19]. Parents commonly report their child’s health and QOL differently from how the child reports it [16,20–22], so a combination of self‐report and parent‐proxy reporting is ideal to give an accurate representation of QOL. Cultural and language adaptations are required, owing to the international nature of many clinical trials, to produce versions that are conceptually equivalent [23]. This includes forward and backward translation, and revalidation with the specific patient group within each culture.…”
Section: Recommendations and Discussionmentioning
confidence: 99%
“…[15,19]. Parents commonly report their child’s health and QOL differently from how the child reports it [16,20–22], so a combination of self‐report and parent‐proxy reporting is ideal to give an accurate representation of QOL.…”
Section: Recommendations and Discussionmentioning
confidence: 99%
“…It has recently been shown that the combination of enoxaparin and antiplatelet therapy can be used as an alternative to oral anticoagulants in the long‐term management of LVAD patients (4). Similarly, satisfactory anticoagulation could be achieved in infants on VAD (3). Nadroparin is routinely used at our department for venous thrombosis prophylaxis and initial anticoagulation of patients after heart valve replacement.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its well‐known bleeding complications, UFH has several limitations (1), including immune‐mediated platelet activation leading to heparin‐induced thrombocytopenia, a variable anticoagulant response requiring continuous anticoagulant monitoring, and the need for venous access that puts patients at risk for infection. Clinical experience with the use of LMWH in mechanical circulatory support is limited (2–4). Here, we evaluated the use of LMWH (nadroparin) as an alternative to UFH in the immediate postoperative period after LVAD implantation.…”
mentioning
confidence: 99%